Fatty Acid Composition and Volatile Profile of M. longissimus thoracis from Commercial Lambs Reared in Different Forage Systems - Ye, Yangfan (Foods, 2020)
Animal production factors can affect the fatty acid and volatile profile of lamb meat. The fatty acid and volatile composition of the M. longissimus thoracis was evaluated from 150 lambs from 10 groups of commercial lambs that differed in age, sex, diet and breed, from three farms, which represent typical forage lamb production systems in New Zealand. The meat from 4-month-old composite lambs slaughtered at weaning had a similar polyunsaturated to saturated fatty acid ratio compared to 6- to 8-month-old composite lambs, but a greater ratio than that of 12-month-old Merino lambs (p < 0.05), with all ratios being lower than the recommended ≥0.45. All lamb production systems produced meat with an omega-6 to omega-3 ratio below 1.5, well below the recommended ratio ≤ 4.0. Meat from 4-month-old lambs had higher C12:0, C14:0 and C16:0 and lower C18:0, reflecting the composition of the milk diet, resulting in higher atherogenic index than meat from other animal groups, while meat from 12-month-old Merino lambs, with lower content of polyunsaturated fatty acids, showed higher thrombogenic index. Meat from lambs processed at weaning contained the greatest concentration of eicosapentaenoic and docosahexaenoic acids, which would qualify as a ‘source’ or ‘good source’ of these target fatty acids based on the Commission of Regulation of the European Union or the Food Standards Australia New Zealand guidelines, respectively. Volatiles were extracted from the headspace of raw lean meat and 36 volatile compounds were identified. The abundance of carbon disulphide, isododecane, heptanal, 2,5-hexanediol and 3-octanone and pentanoic, octanoic, nonanoic and heptanoic acids was similar between all groups of lambs. Meat from 12-month-old Merino lambs had low abundance of acetic, propanoic, butanoic and hexanoic acids, and hexanal, octanal and dimethyl sulphide. For 6- to 8-month-old composite lambs, hexanal, octanal and nonanal were present at higher relative abundance in meat from lambs that grazed on chicory than perennial ryegrass. The significant differences in the fatty acid and volatile profiles in meat from 12-month-old Merino lambs compared with lambs slaughtered at weaning or further grazed on red clover, chicory or mixed pasture may result in distinctive nutritional value and lamb flavour.